2016
DOI: 10.1080/09512748.2016.1264455
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Islamic banking and finance: a comparison of its development and governance in Malaysia and Singapore

Abstract: In response to the limited engagement with critical social science concerning the governance of Islamic banking and finance (IBF), this paper compares and conceptualizes the development and governance of IBF in Malaysia and Singapore. We argue that IBF governance in Malaysia and Singapore can be distinguished on the basis of ethnic politics, moral suasion, product demand, product innovation, and the character of state practices. Concerning the latter, we contend that the political economy of both countries can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The development of Islamic banking and finance in Malaysia is motivated by two interconnected policy objectives. First, Islamic banking and finance is developed as a neoliberal ethnic-religious policy to promote financial inclusion and prioritisation of economic benefits for the majority Muslim Malays (termed bumiputra ) 3 (Lai, 2015; Lai and Samers, 2017). Second, Islamic finance development would enable Malaysia to expand and diversify its financial sector in an Islamic-compliant manner (Poon et al, 2018; Rethel, 2018).…”
Section: Developing Green Sukuk To Advance An Islamic Finance Frontiermentioning
confidence: 99%
See 2 more Smart Citations
“…The development of Islamic banking and finance in Malaysia is motivated by two interconnected policy objectives. First, Islamic banking and finance is developed as a neoliberal ethnic-religious policy to promote financial inclusion and prioritisation of economic benefits for the majority Muslim Malays (termed bumiputra ) 3 (Lai, 2015; Lai and Samers, 2017). Second, Islamic finance development would enable Malaysia to expand and diversify its financial sector in an Islamic-compliant manner (Poon et al, 2018; Rethel, 2018).…”
Section: Developing Green Sukuk To Advance An Islamic Finance Frontiermentioning
confidence: 99%
“…Second, Islamic finance development would enable Malaysia to expand and diversify its financial sector in an Islamic-compliant manner (Poon et al, 2018; Rethel, 2018). This strategy of meeting ethnic-religious goals through the promotion of neoliberal market mechanisms has been referred to as ‘ordoliberalism’, through which Malaysia has established itself as an international Islamic financial centre (Lai and Samers, 2017). From the establishment of the country's first Islamic bank in 1983, to expanding Malaysia's influence over global Islamic finance development more recently, the state has employed classic ‘industrial policies’, such as standard setting, tax incentives, and adoption of new products by government agencies to boost the development of the sector (Lai, 2015).…”
Section: Developing Green Sukuk To Advance An Islamic Finance Frontiermentioning
confidence: 99%
See 1 more Smart Citation
“…Authors [50] described that the satisfying of customers hold clients for the higher productivity, higher portion of the overall industry and more rate of return. Moreover, authors [72] examined that service quality fills in as contribution to show up as consumer loyalty. Likewise, authors [48] found that customer satisfaction produces many results like rehash buy; unwaveringness, positive word of mouth and long lasting returns.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…A side of these is an Islamic bank that runs all the activities of banking, but it restricted its services within the confine of Islamic Law which prohibits the acceptances and distributions of interest (riba). Prior to the establishment of Islamic banking the world over, about 4 decades ago, the only existing banking system was the conventional one, which operates under a secular system, but the inception of the Islamic banking system brought about a rapid change in the global financial structure, which trimmed the monopolistic status enjoyed by the conventional banks, and created a competitive environment for the banks [67].…”
Section: Islamic Bankingmentioning
confidence: 99%